1991
DOI: 10.1007/bf02924606
|View full text |Cite
|
Sign up to set email alerts
|

Complex tunica albuginea cyst simulating an intratesticular lesion

Abstract: Cysts of the tunica albuginea are uncommon lesions of the testis which in all reported cases have been benign. Complex cysts of the tunica albuginea can mimic intratesticular lesions, thus necessitating orchiectomy. We present a case of a complex tunica albuginea cyst which mimicked an intratesticular lesion at sonography, as well as at magnetic resonance imaging (MRI). Tangential views, however, suggested that this was in fact an extratesticular lesion. The use of tangential views, as well as knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Simple cysts of the tunica albuginea may be followed conservatively, but complex cysts sonographically are highly suggestive of malignancy. 8 The epidermoid cyst is an uncommon lesion composed histologically of a fibrous cyst wall with squamous epithelium surrounding a cavity containing keratinized debris. This may ap~ear sonographically as either a solid echogenic mass or a predominantly cystic lesion with few internal echoes.1° The adenomatoid tumor is the most common paratesticular tumor, usually appearing as a solid echogenic epididymal mass, but rarely it may arise in the tunica albuginea as well, mimicking testicular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Simple cysts of the tunica albuginea may be followed conservatively, but complex cysts sonographically are highly suggestive of malignancy. 8 The epidermoid cyst is an uncommon lesion composed histologically of a fibrous cyst wall with squamous epithelium surrounding a cavity containing keratinized debris. This may ap~ear sonographically as either a solid echogenic mass or a predominantly cystic lesion with few internal echoes.1° The adenomatoid tumor is the most common paratesticular tumor, usually appearing as a solid echogenic epididymal mass, but rarely it may arise in the tunica albuginea as well, mimicking testicular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…They develop in the tunica albuginea and may be single or multiple; they are believed to arise from the mesothelial cells of the tunica itself [9]. At US examination albuginea cysts appear well-defined [10]; they develop in the virtual space of the vaginal cavity and cause signs of compression of the adjacent testicular parenchyma (Fig.…”
Section: Albuginea Cystmentioning
confidence: 99%
“…Poster et al[13] reported a benign complex TA cyst where the echogenic material proved to be inflammatory debris on pathological examination after orchiectomy.…”
Section: Spectrum Of Sonographic Featuresmentioning
confidence: 99%